Find My Things: Personalized Accessibility through Teachable AI for People who are Blind or Low Vision - Wen, Linda Yilin; Morrison, Cecily; Grayson, Martin; Faia Marques, Rita; Massiceti, Daniela; Longden, Camilla; Cutrell, Ed (Extended Abstracts of the CHI Conference on Human Factors in Computing Systems, 2024)
The opportunity for artificial intelligence, or AI, to enable accessibility is rapidly growing, but widely impactful applications can be challenging to build given the diversity of user need within and across disability communities. Teachable AI systems give users with disabilities a way to leverage the power of AI to personalize applications for their own specific needs. We demonstrate Find My Things as an end-to-end example of applying Teachable AI systems to address the diversity of accessibility needs. An application that can be taught by people who are blind or low vision to find their personal things, Find My Things illustrates the potential Teachable AI holds for accessibility.